PROSPECTS OF INSTITUTIONAL DEVELOPMENT OF THE NON-GOVERNMENTAL SECTOR: ANALYSIS OF THE DRAFT NATIONAL STRATEGY FOR CSI DEVELOPMENT - Dmytrenko, Olena (International Journal of Innovative Technologies in Social Science, 2020)
This study is devoted to the analysis of the draft National Strategy for the Development of Civil Society Institutions in Ukraine for 2021-2025. The developed document has already been presented to the public and is being discussed in the regions of the country. A positive trend in this aspect is the procedure of developing and harmonizing the content of the Strategy with the involvement of a wide range of stakeholders. According to the results of the analysis, we found that the strategic directions of civil society development in the country have not changed since 2016, although the new Strategy sets clearer goals. Dividing the tasks of the Strategy by the nature of their implementation, we found that the greatest efforts over the next five years will be aimed at improving the regulatory and legal support of CSOs (37.9% of tasks). The cross-cutting theme of the whole document was the development of the foundations for the crystallization of the NGOs into a full-fledged economic player and bringing the activities in the non-governmental sector to the professional level. It was found that in practice, the non-governmental sector over the past four years has increased its potential as a provider of services to the state on market terms. Although they noted low activity among regional NGOs during the discussion of the basic document for them. This, in turn, raises the issue of communication support for the implementation of the Strategy, as well as raises the issue of the quality system of its monitoring and evaluation.